2020
DOI: 10.21203/rs.2.23342/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of 3D genome organization, guided by cohesin and CTCF looping, on sex-biased chromatin interactions and gene expression in mouse liver

Abstract: Several thousand sex-differential distal enhancers have been identified in mouse liver; however, their links to sex-biased genes and the impact of any sex-differences in nuclear organization and chromatin interactions are unknown. To address these issues, we first characterized 1,847 mouse liver genomic regions showing significant sex differential occupancy by cohesin and CTCF, two key 3D nuclear organizing factors. These sex-differential binding sites were primarily distal to sex-biased genes but rarely gener… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 82 publications
(173 reference statements)
1
4
0
Order By: Relevance
“…When looking into the TFs that mediate estradiol's effects in XYM for potential male-biased regulation in adipose tissue, we found matches with 13 of the top 20 TFs from the Anderson et al ( 2020) human adipose study. These included AR, CTCF, SMC1A, EZH2, ESR1, RAD21, and TP63, and many were also consistent in additional mouse Matthews and Waxman 2020) and human studies including GTEx Oliva et al 2020).…”
Section: Transcription Factor Network Analysissupporting
confidence: 59%
“…When looking into the TFs that mediate estradiol's effects in XYM for potential male-biased regulation in adipose tissue, we found matches with 13 of the top 20 TFs from the Anderson et al ( 2020) human adipose study. These included AR, CTCF, SMC1A, EZH2, ESR1, RAD21, and TP63, and many were also consistent in additional mouse Matthews and Waxman 2020) and human studies including GTEx Oliva et al 2020).…”
Section: Transcription Factor Network Analysissupporting
confidence: 59%
“…To determine whether the non-uniform SNPs can result in variations in TF binding between CD-1 individuals, we used a CTCF ChIP-seq dataset that was taken from the liver of four male and four female CD-1 individuals [5]. Upon examination, replicate 4 of the male, and replicate 4 of the female, appeared globally to be of lower quality than the other replicates (Additional file 1: Figure S2A); thus, these two replicates were removed from consideration.…”
Section: Resultsmentioning
confidence: 99%
“…We then determined peaks that were ir-reproducible between the remaining replicates (Additional file 1: Figure S2B; see Methods) and took these as candidates for regions where there could be variability in Ctcf binding between individuals. The study that generated these ChIP-seq datasets identified regions of sexual dimorphism in Ctcf binding [5], and these were excluded from the set of considered ir-reproducible peaks. We reasoned that it was possible that not all sexually dimorphic regions were identified.…”
Section: Functional Consequences Of Genotype Variation Between Cd-1 I...mentioning
confidence: 99%
See 1 more Smart Citation
“…The sex bias in the mutation burden of the cancer genomes was associated with decreased gene expression in DNA mismatch repair [ 44 ], suggesting that lower efficiency of genome repair mechanisms might underlie sex differences in the frequency of mutations [ 47 , 48 ]. Moreover, recent studies are showing that two main regulators of genome topology (i.e., CTCF and COHESIN) bind chromatin in a sex-specific manner [ 49 , 50 ] and that mutations at CTCF binding sites can act as tumor drivers [ 51 ]. Sex-specific chromatin conformations might, therefore, affect the efficiency with which DNA damage is repaired, providing a further mechanistic explanation for sex differences in tumor development.…”
Section: Sex Disparities In Genetic and Epigenetic Regulationsmentioning
confidence: 99%